Motivational Schemes and Employees Job Design of a Manufacturing Company - Berganio, Gina D.; Unico, Maricris G.; Pendon III, Fernando T. (International Journal of Research in Interdisciplinary Studies, 2025)
Employees play a crucial role in an organization’s success, contributing their skills, knowledge, and commitment to achieving business goals. Their dedication makes them indispensable, yet remuneration alone may not be enough to sustain motivation. Organizations must implement strategic initiatives to encourage employees to consistently perform at their best. This study aims to assess the impact of motivational schemes on employee performance at EMD Technologies Philippines Inc., a manufacturing company in Calamba, Laguna. Using a Quantitative Research Design with a Descriptive Correlational approach, the study examines the relationship between motivational schemes and job design. Stratified Random Sampling was employed to categorize respondents into lower- and middle-level employees. The research is anchored in Maslow’s Hierarchy of Needs, highlighting the motivational factors affecting performance, and the Job Characteristics Model (JCM), which enhances job satisfaction through effective job design. Findings indicate a stable workforce with extensive tenure and specialized roles, providing valuable insights into employee engagement. However, lower scores in love and belonging, self-esteem, and self-actualization suggest areas for improvement in fostering interpersonal connections, confidence, and professional growth. Additionally, limited skill variety highlights the need to enhance job diversity. To address these concerns, the study recommends sustaining strategies such as employee development programs, retention initiatives, health and wellness efforts, recognition programs, career advancement opportunities, diversity and inclusion efforts, empowerment in decision-making, workplace safety improvements, continuous evaluation, and fostering a supportive organizational structure. Implementing these strategies can enhance motivation, job satisfaction, and productivity, ultimately driving long-term success.